Influence of vacuum packaging on certain chemical qualities of mutton" - DUSHYANTHAN, K; SHANMUGAM, A M; VENKATARAMANUJAM, V (The Indian Journal of Animal Sciences, 2014)
The influence of vacuum packing on extract release volume (ERv); thiobarbituric acid (TBA) number and tyrosine value (TV) of mutton packed under 2 methods, in 4 packaging materials and stored for different periods under chiller(5Â±2Â°C) and freezer (-10'C) temperatures, was studied. Mutton packed under vacuum and stored at both chiller andfreezer temperatures revealed higher ERV and lower TBA number and TV. Multilayer (ML) material was the mostsuitable material for packaging mutton under vacuum and storing at both chiller and freezer temperatures. Mutton packed in ML material had the highest ERV and the lowest TBA number and TV. The anaerobic environment created by thevacuum method and the barrier properties of ML material for oxygen led to the lower proteolysis. As the storage periodincreased at both chiller and freezer temperature there was an increase in TBA number and TV of mutton, whereas ERVof mutton decreased with increase in storage at chiller temperatures and increased with increase in storage at freezertemperatures. The influence of vacuum packaging has brought about a better effect by improving the ERV, TBA numberand TV of mutton.